2023
DOI: 10.3390/ijms24086944
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microbial Consortia Catalysis Strategy for the Production of Hydroxytyrosol from Tyrosine

Abstract: Hydroxytyrosol, a valuable plant-derived phenolic compound, is increasingly produced from microbial fermentation. However, the promiscuity of the key enzyme HpaBC, the two-component flavin-dependent monooxygenase from Escherichia coli, often leads to low yields. To address this limitation, we developed a novel strategy utilizing microbial consortia catalysis for hydroxytyrosol production. We designed a biosynthetic pathway using tyrosine as the substrate and selected enzymes and overexpressing glutamate dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Enzymes such as HpaBC, which involves two cofactor cycles, are often targeted for cofactor engineering. Establishing a cycle of NADH by the exogenous addition of nicotinamide or the utilization of TyrA can replenish NADH supply, increasing hydroxytyrosol production. , Increasing FADH 2 supplementation by the introduction of LAAD successfully enhanced the efficiency of hydroxylation, resulting in an 112% increase in hydroxytyrosol production. It is worth mentioning that due to the promiscuous catalytic activities of the enzymes in the pathway, the de novo biosynthesis of hydroxytyrosol is based on 4-hydroxyphenylpyruvate as a node, and hydroxytyrosol is synthesized through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymes such as HpaBC, which involves two cofactor cycles, are often targeted for cofactor engineering. Establishing a cycle of NADH by the exogenous addition of nicotinamide or the utilization of TyrA can replenish NADH supply, increasing hydroxytyrosol production. , Increasing FADH 2 supplementation by the introduction of LAAD successfully enhanced the efficiency of hydroxylation, resulting in an 112% increase in hydroxytyrosol production. It is worth mentioning that due to the promiscuous catalytic activities of the enzymes in the pathway, the de novo biosynthesis of hydroxytyrosol is based on 4-hydroxyphenylpyruvate as a node, and hydroxytyrosol is synthesized through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous strategies have been applied in attempts to improve the efficiency of microbial synthesis of hydroxytyrosol, including blocking the competitive pathways and directed evolution of key enzymes. The titer of hydroxytyrosol has been greatly improved in some recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the knockout of endogenous aromatic aldehyde oxidase was employed to prevent the formation of by-products, resulting in the nearly complete synthesis of HT in engineered E. coli . Other studies [ 42 , 43 ] have utilized E. coli strains carrying specific hydroxylases to synthesize HT, resulting in notable yields of HT through strain optimization.…”
Section: Production Via Gmosmentioning
confidence: 99%
“…This approach not only highlights the synergistic potential of co-culturing strategies but also points to future directions in microbial consortium engineering for biomanufacturing. In another study, Gong et al [ 43 ] developed a novel approach to improve the production of HT. The strategy involved designing a biosynthetic pathway using tyrosine as the substrate and selecting specific enzymes.…”
Section: Production Via Gmosmentioning
confidence: 99%
“…Therefore, it is important to apply strategies such as protein engineering to improve the substrate specificity. It has been reported that a fractional reaction using separately cultured cells can weaken the shunt of the end product [115]. However, there is a lack of effective strategies for the efficient and sustainable synthesis of plant polyphenols.…”
Section: Summary and Future Outlookmentioning
confidence: 99%